The Effect of Pull-Up Training on Smash Performance in Volleyball Extracurricular Activities at SMA Negeri 1 Sungai Pinang - Firdaus, Ridho; Putri, Siti Ayu Risma; Kristina, Putri Cicilia (Physical Education, Health and Recreation Study Program, Universitas Insan Budi Utomo, Indonesia, 2025)
This study aims to determine whether pull-up training has a significant effect on the volleyball smash performance of students participating in the extracurricular volleyball program at SMA Negeri 1 Sungai Pinang. The research employed an experimental (quantitative) method with a pre-experimental design, specifically the one-group pretest-posttest design. The population consisted of 12 male students who were active members of the school's volleyball extracurricular activity. The sampling technique used was total sampling. The data collection techniques employed in this study included observation, testing, and documentation. The data analysis technique employed in this study utilized inferential statistics, specifically the Paired Sample t-test, which SPSS assisted. The results of the Paired Sample t-test analysis showed a t-count value of -8.424 with degrees of freedom (df) = 11, and N-1 and a significance value (p-value) of 0.001. The significance value (p-value) is 0.001, which is smaller than 0.05 (0.001 < 0.05). This means that H0 is rejected, and Ha is accepted. Therefore, pull-up training has a significant effect on improving smash performance in volleyball among students participating in the extracurricular program at SMA Negeri 1 Sungai Pinang.